2021
DOI: 10.48550/arxiv.2107.07917
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Mapping Lyman-alpha forest three-dimensional large scale structure in real and redshift space

Abstract: This work presents a new physically-motivated supervised machine learning method, hydro-bam, to reproduce the three-dimensional Lyman-α forest field in real and in redshift space learning from a reference hydrodynamic simulation, thereby saving about 7 orders of magnitude in computing time. We show that our method is accurate up to k ∼ 1 h Mpc −1 in the one-(PDF), two-(power-spectra) and three-point (bi-spectra) statistics of the reconstructed fields. When compared to the reference simulation including redshif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 76 publications
0
5
0
Order By: Relevance
“…The range of scales accurately mapped with this method is well beyond the resolution of next-generation observations (Walther et al 2021), as well as that of alternate machinelearning-based approaches for modeling Lyα forest (Sinigaglia et al 2021). Our method provides an alternative to running costly hydrodynamical simulations for mock catalog generation and the construction of Lyα power-spectra emulators.…”
Section: Discussionmentioning
confidence: 99%
“…The range of scales accurately mapped with this method is well beyond the resolution of next-generation observations (Walther et al 2021), as well as that of alternate machinelearning-based approaches for modeling Lyα forest (Sinigaglia et al 2021). Our method provides an alternative to running costly hydrodynamical simulations for mock catalog generation and the construction of Lyα power-spectra emulators.…”
Section: Discussionmentioning
confidence: 99%
“…Note that in a companion paper (Horowitz et al 2021), convolutional neural networks have also been used to synthesize hydrodynamic fields conditioned on dark matter fields from N-body simulations, which might be very useful for the rapid generation of mocks. Similarly, Sinigaglia et al (2021) has developed a new physically-motivated supervised machine learning method (HYDRO-BAM) from a reference hydrodynamical simulation of comoving side 100 Mpc/h. The PDF, 3d power spectrum and bi-spectra can be reconstructed with error of a few percent up to modes k= 0.9 Mpc/h.…”
Section: Discussionmentioning
confidence: 99%
“…Fig. 5 of Sinigaglia et al (2021)). But 3d Ly-α forest surveys also enable precise measurements of flux correlations at much smaller scales where the FGPA might not be adequate.…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…The study by [23], using high mass halos (halos with ≳ 10 12 M ⊙ h −1 in a 1,5 h −1 Gpc side cubical volume), showed that a proper modelling of the higher order statistics requires going to at least third-order non-local bias, and that this can be done through the cosmic web classification. These findings were exploited in the context of effective baryonic physics bias mapping and Lyman-α forest modelling (see [36][37][38]). This paper extends previous PATCHY versions with a novel hierarchical cosmic web classification, indirectly accounting for both long-and short-range non-local bias at least up to third order.…”
Section: Jcap07(2024)083mentioning
confidence: 99%